Postnatal intermittent hypoxia enhances phrenic and reduces vagal upper airway motor activities in rats by epigenetic mechanisms - Bittencourt-Silva, Paloma G. [UNESP]; Menezes, Miguel Furtado [UNESP]; Mendonça-Junior, Bolival A. [UNESP]; Karlen-Amarante, Marlusa [UNESP]; Zoccal, Daniel B. [UNESP] (Wiley, 2020)
New Findings: What is the central question of this study? What are the alterations in respiratory motor activity that may underlie ventilatory dysfunctions in juvenile and adult animals exposed to postnatal chronic intermittent hypoxia? What is the main finding and its importance? Postnatal chronic intermittent hypoxia modifies the motor activity to pumping and upper airway respiratory muscles in rats, mediated by epigenetic DNA hypermethylation, enhancing resting pulmonary ventilation and predisposing to collapse of the upper airways in juvenile and adult life. Abstract: Periods of apnoea, commonly observed in prematures and newborns, are an important risk factor for the development of cardiorespiratory diseases in adulthood. In the present study, we evaluated changes in pulmonary ventilation and respiratory motor pattern in juvenile and adult rats exposed to postnatal chronic intermittent hypoxia (pCIH). Newborn male Holtzman rats (P1) were submitted to pCIH (6% O2 for 30 s, every 9 min, 8 h a day (09.30–17.30 h)) during their first 10 days of life, while control animals were maintained under normoxic conditions (20.8% O2). Thereafter, animals of both groups were maintained under normoxia until the experiments. Unanaesthetized juvenile pCIH rats (n = 27) exhibited elevated tidal volume and respiratory irregularities (P < 0.05) compared to control rats (n = 7). Decerebrate, arterially perfused in situ preparations of juvenile pCIH rats (n = 11) displayed augmented phrenic nerve (PN) burst amplitude and reduced central vagus nerve activity in comparison to controls (n = 10). At adulthood, pCIH rats (n = 5) showed enhanced tidal volume (P < 0.05) and increased respiratory variability compared to the control group (n = 5). The pCIH-induced changes in ventilation and respiratory motor outputs were prevented by treatment with the DNA methyltransferase inhibitor decitabine (1 mg kg−1, i.p.) during the exposure to pCIH. Our data demonstrate that pCIH in rats impacts, in a persistent way, control of the respiratory pattern, increasing PN activity to the diaphragm and reducing the vagal-related activity to laryngeal muscles, which, respectively, may contribute to improve resting pulmonary ventilation and predispose to collapse of the upper airways during quiet breathing.
Keywords: breathing; DNA methylation; hypoxia; postnatal development